Overcoming Symmetry Mismatch in Vaccine Nanoassembly through Spontaneous Amidation. Issue 1 (27th October 2020) - Rahikainen, Rolle; Rijal, Pramila; Tan, Tiong Kit; Wu, Hung‐Jen; Andersson, Anne‐Marie C.; Barrett, Jordan R.; Bowden, Thomas A.; Draper, Simon J.; Townsend, Alain R.; Howarth, Mark
Abstract: Matching of symmetry at interfaces is a fundamental obstacle in molecular assembly. Virus‐like particles (VLPs) are important vaccine platforms against pathogenic threats, including Covid‐19. However, symmetry mismatch can prohibit vaccine nanoassembly. We established an approach for coupling VLPs to diverse antigen symmetries. SpyCatcher003 enabled efficient VLP conjugation and extreme thermal resilience. Many people had pre‐existing antibodies to SpyTag:SpyCatcher but less to the 003 variants. We coupled the computer‐designed VLP not only to monomers (SARS‐CoV‐2) but also to cyclic dimers (Newcastle disease, Lyme disease), trimers (influenza hemagglutinins), and tetramers (influenza neuraminidases). Even an antigen with dihedral symmetry could be displayed. For the global challenge of influenza, SpyTag‐mediated display of trimer and tetramer antigens strongly induced neutralizing antibodies. SpyCatcher003 conjugation enables nanodisplay of diverse symmetries towards generation of potent vaccines. Abstract : Nanoassembly can play a key role in generating effective vaccines for emerging (SARS‐CoV‐2) and established (influenza) pandemic threats. SpyTag‐mediated display was used to adapt the nanocage to the challenge of bacterial or viral antigens with diverse cyclic and dihedral symmetries. Establishing display of both trimeric and tetrameric antigens may lead to an influenza vaccine with broader protection.